Bolted joint integrity monitoring with second harmonic generated by guided waves. (January 2019) - Yang, Yi; Ng, Ching-Tai; Kotousov, Andrei
In this study, the second harmonic generation due to the contact nonlinearity caused by bolt loosening is studied experimentally and numerically using three-dimensional explicit finite element simulations. In particular, it is demonstrated that the magnitude of the second harmonic generation normally increases with the loosening of the bolted joint, and there is a reasonable agreement between the numerical simulations and experimental results. The finite element model, which was validated against the experimentally measured data, is further utilized to investigate an important practical situation when a loosened bolt is weakened by fatigue cracks located at the edge of the hole. The numerical case studies show that the contact nonlinearity and the change of the behaviour of the second harmonic generation with the tightening level are very different to the corresponding results with the fatigue cracks. This identified difference in the second harmonic generation behaviour can serve as an indicator of the bolted joint integrity and thus provide early warning for engineers to make decision on the necessity of carrying out further safety inspections. Overall, the findings of this study provide improved physical insights into second harmonic generation for bolt loosening, which can be used to further advance damage detection techniques using nonlinear guided waves.